Investigating the fragmentation of students’ creative thinking structures in realistic mathematics education: A qualitative case study of junior high school students - Santosa, Yoga Tegar; Setyaningsih, Nining; Sukowati, Berliani Ardelia; Maulida, Dini Wardani; Mahmudah, Mutiara Hisda; Meganingrum, Ade Ayu (Jurnal Elemen, 2026)
The fragmentation of creative thinking structures is a phenomenon requiring serious attention in Realistic Mathematics Education (RME). However, studies that systematically explore how students’ creative thinking fragmentation manifests across RME learning stages remain limited. This study aims to examine the types and forms of students' creative thinking fragmentation across four RME activities: situation, model of situation, model for knowledge, and formal mathematics. This research employs a qualitative case study design. Participants consisted of 18 seventh-grade students from an Integrated Islamic Junior High School in Sukoharjo Regency. Data were collected through non-routine mathematical problem tests and in-depth interviews, with validity ensured through source triangulation. Data analysis involved thematic coding based on a fragmentation typology aligned with RME stages, followed by data reduction, display, and conclusion drawing. The results identified five types of fragmentation: (1) less-strict fragmentation at the situation stage, (2) translational fragmentation (text to symbol) at the situation stage, (3) pseudo-false fragmentation at the model of situation stage, (4) translational fragmentation (text to image) at the model for knowledge stage, and (5) pseudo-true fragmentation at the formal mathematics stage. These findings extend theoretical perspectives and inform instructional design and scaffolding strategies in RME classrooms.